Postępy w diagnostyce i leczeniu operacyjnym zeza u młodzieży i dorosłych - Broniarczyk-Loba, Anna; Nowakowska, Olimpia; Laudańska-Olszewska, Iwona; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Purpose: To present complete process of pre-operative strabismus diagnosis, which can be used for prediction of post-operative diplopia in adolescents and adults. Material and methods: The study involved three patients, who were qualified for the surgical treatment of strabismus. Complete pre-operative diagnosis predicting potential post-operative diplopia was performed in all patients. The prismatic test for diplopia, hyperfunctional muscle botuline toxin injection, and prism correction were performed. Results: Regarding the results of tests, two patients were qualified for surgical treatment. None of them suffered from diplopia after this treatment. The third patient in pre-operative tests showed unacceptably high risk of intolerable diplopia. Conclusions: Post-operative diplopia in adolescents and adults represents a serious problem, especially in susceptible patients. Accurate and complete pre-operative diagnosis allows for risk reduction in post-operative diplopia. The predictive test for post-operative diplopia, botuline toxin injection and prism correction in isolation are not always able, to give a reliable indication, as to the sensory status following strabismus surgery. A combination of the three above mentioned techniques give more reliable diagnosis. For patients, who can possibly suffer from post-operative diplopia, the adjustable suture technique should be applied.